2022
DOI: 10.3389/fnins.2022.980135
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative collateral score for the prediction of clinical outcomes in stroke patients: Better than visual grading

Abstract: ObjectivesTo identify preoperative prognostic factors for acute ischemic stroke (AIS) patients receiving mechanical thrombectomy (MT) and compare the performance of quantitative collateral score (qCS) and visual collateral score (vCS) in outcome prediction.MethodsFifty-five patients with AIS receiving MT were retrospectively enrolled. qCS was defined as the percentage of the volume of collaterals of both hemispheres. Based on the dichotomous outcome assessed using a 90-day modified Rankin Scale (mRS), we compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The mean rCBV (relative CBV) showed a high and statistically significant correlation with functional outcome (Figure 1). The Miteff Score correlates best with the mean rCBV, followed by the Maas Score, which reflects their good usefulness prediction of the functional outcome [51].…”
Section: Manual Assessmentmentioning
confidence: 72%
See 1 more Smart Citation
“…The mean rCBV (relative CBV) showed a high and statistically significant correlation with functional outcome (Figure 1). The Miteff Score correlates best with the mean rCBV, followed by the Maas Score, which reflects their good usefulness prediction of the functional outcome [51].…”
Section: Manual Assessmentmentioning
confidence: 72%
“…The mean rCBV (relative CBV) showed a high and statistically significant correlation with functional outcome (Figure 1). The Miteff Score correlates best with the mean rCBV, followed by the Maas Score, which reflects their good usefulness prediction of the functional outcome [51]. In a study conducted by Yeo et al, it was demonstrated that, among the various grading systems, only the Miteff grading system exhibited reliability in identifying both favorable and poor outcomes in patients with anterior circulation acute ischemic stroke treated with IVT.…”
Section: Manual Assessmentmentioning
confidence: 91%